Post-Infection Oscillometry and Pulmonary Metrics in SARS-CoV-2 Patients: A 40-Day Follow-Up Study - Noemi Suppini; Cristian Oancea; Ovidiu Fira-Mladinescu; Daniel Traila; Camelia Pescaru; Monica Steluta Marc; Diana Manolescu; Emanuela Vastag; Ayesha Ali; Elena Hogea; Ciprian Nicolae Pilut (Diseases, 2023)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has had significant impacts on pulmonary function. This study aimed to comprehensively evaluate pulmonary function and structure in patients 40 days post-SARS-CoV-2 infection, employing an array of testing methodologies including spirometry, plethysmography, forced oscillometry, and CT scanning. It also sought to establish potential correlations between these metrics and evaluate if forced oscillometry could provide additional value in post-infective lung function assessment. A 40-day post-infection follow-up observational study was conducted involving 66 patients with confirmed SARS-CoV-2 infection. The results revealed decreases in FVC and FEF25–75 with the increasing severity of COVID-19. Specifically, patients with severe symptoms exhibited statistically significant decreases in FVC (mean = 86.8) compared with those with mild symptoms (mean = 106.0; p = 0.018). The FEF25–75 showed a similar trend, with severe patients exhibiting a mean of 77.7 compared with 82.9 in the mild group (p = 0.017). Furthermore, resonant frequency (RF) increased with disease severity, with the severe group exhibiting a statistically significant increase (mean = 17.4) compared with the mild group (mean = 14.3; p = 0.042). CT scans showed an increase in ground-glass opacities with disease severity, with 81.8% of severe patients demonstrating this finding (p = 0.037). Multiple regression analysis revealed that Reactance at 4 Hz (X4), Forced Expiratory Flow 25–75% (FEF25–75), and Resonant Frequency (RF) were significantly related to COVID-19 severity. Specifically, for each unit increase in these factors, the risk of the event was estimated to increase by a factor of 3.16, 2.09, and 1.90, respectively. Conversely, Resistance at 4 Hz (R4) and Airway Resistance (RAW) were found to significantly decrease the event hazard, highlighting their potential protective role. Spirometry, plethysmography, and forced oscillometry are effective in assessing these changes. Forced oscillometry may be particularly beneficial in identifying subtle changes in lung function post-COVID-19. Further studies are warranted to validate these findings and develop strategies to manage post-infective pulmonary changes in SARS-CoV-2 patients.